Observing the Sabbath: Rest, Bodily Practice, and the Debate about “Judaizing” in Reformation Germany - Diemling, Maria (Reformation, 2025)
This article compares the Sabbath discourse in a tract on the observance of the Sabbath and statutory holidays (Von dem Sabbbat und geboten feyertagen, 1524) by the Protestant reformer Andreas Karlstadt (1486–1541) with a book about Jewish rituals (Der Gantz Jüdisch Glaub, 1530) by the convert from Judaism, Anthonius Margaritha (1492/1498–1542). Focusing on the bodily practice of rest, the article examines the idea of holiness, the Sabbath as a social institution, and the disciplined body resting on the Sabbath. It explores whether contemporary Jewish observance of the Sabbath with its focus on the biblically commanded practice of rest played a role in the Reformers’ quest for biblical authenticity. The article confirms that Judaism remained a critical reference point for Christian theologians but actual Jewish practice was dismissed as “carnal” and subversive. The accusation of “judaizing” served as a powerful rhetorical device to undermine a Christian opponent’s theological position.